Factors Influencing Eating and Taking Iron Supplement Behaviors for Anemia Prevention in Pregnant Women - Waeberaheng, Waenureeyah; Chatchawet, Warangkana; Kritcharoen, Sureeporn (Princess of Naradhiwas University Journal, 2019)
This predictive research on anemia prevention in pregnant women aimed to: 1) study level of eating and taking iron supplement behaviors, and 2) identify factors for prediction of perceived risk of anemia, perceivedseverityofanemia,perceivedbenefitofanemiaprevention,perceivedbarrierstoanemiapreventive behavior, and knowledge about anemia among pregnant women. The sample consisted of 150 pregnant women who were receiving care at the Antenatal Care Clinic of the Regional Health Promotion Center 12 in Yala. The research instrument consisted of 7 questionnaires: 1) general information, 2) perceived risk of anemia pregnancy, 3) perceived severity of anemia pregnancy, 4) perceived benefit of anemia prevention, 5) perceived barriers to anemia preventive behavior, 6) knowledge about anemia, and 7) eating and taking iron supplement behaviors for anemia prevention. Content validity of questionnaires was approved by three experts. Reliability of questionnaires number 2-5 and 7 was tested using Cronbach’s alpha coefficient, yielding values of 0.81, 0.81, 0.82, 0.87 and 0.89, respectively. The reliability of knowledge of anemia questionnaire was tested using Kuder-Richardson (KR-20), with a given value of 0.77. Data were analyzed using percentage, mean and standard deviation. Predictability was analyzed using multiple regression. Result showed that the overall level of eating and taking iron supplement behaviors for anemia prevention in pregnant women was at a good level (M = 64.63, S.D. = 7.23). Regression modeling showed that perceived barriers for anemia preventive behavior and knowledge of anemia could predict 29 percent of the variation (Adjusted R2 = .29, p < .001). The result of this study could be data-based for improving model of promoting eating and taking iron supplement behaviors for anemia prevention in pregnant women.